Ukrainian industry perspectives on the global market of the manufacturing outsourcing - Gorova, Kseniia (L'Association 1901 "SEPIKE", Deutschland, 2015)
The article describes an expediency of the access to the global market of the manufacturing outsourcing by Ukrainian industrial enterprises, premises and obstacles of this process. Political and economic instability, "black" economy and unstable legal framework, crisis and unstable financial status of many companies reduce the competitiveness of Ukraine on the outsourcing market. But a large number of research organizations, powerful industrial enterprises and a significant amount of skilled labor create good prerequisites for Ukraine's stable position in the global outsourcing market. The article offers such areas of the outsourcing services provision as: research and development outsourcing, certain parts of the production process outsourcing, assembly operations outsourcing, full manufacturing outsourcing.
Keywords: manufacturing outsourcing; industry; enterprise; outsourcing global market